Silica: An efficient catalyst for one-pot regioselective synthesis of dithioethers - Kundu, Samir; Roy, Babli; Basu, Basudeb (Beilstein Journal of Organic Chemistry, 2014)
The development of a silica-promoted highly selective synthesis of 1,2 or 1,3-dithioethers via solvent-free one-pot tandem reactions of an allyl bromide with excess thiol at room temperature is described. The choice of silica gel, either pre-calcined or moistened with water, exhibited notable regioselectivity in the formation of dithioethers. Plausible mechanistic routes were explored and postulated.
Keywords: allyl halide; dithioether; silica gel; tandem reactions; thiol